The shock of the light - Inglis Hall, Lori (Pamela Dorman Books, 2026)
"Twins Tessa and Theo are roots of the same tree, in tune with one another's every thought and desire. As World War II takes hold across Europe, both are eager to do their part. Theo is recruited by the RAF and disappears into the skies, while Tessa jumps at the chance to join the Special Operations Executive, devoted to spying and sabotage behind enemy lines. It will be dangerous, highly classified work, but Tessa, despite all she shares with Theo, is no stranger to secret-keeping. Two years later, Theo comes home. Tessa does not. Theo, wounded, broken by the loss of his fellows and his sister, is indefatigable, angry, driven, a clandestinely gay man at a time when homosexuality was illegal--and he will pay a price for pursuing answers about Tessa's fate. Decades later, PhD candidate Edie is deep into her research on the Special Operations Executive during the war. When she finds Theo in London, they form an unlikely partnership, and together they finally uncover the truth about Theo's beloved sister--a truth that stretches back to the summer Tessa spent in France before the war had even begun"-- Provided by publisher.